Low cost management of replicated data - Joseph, Thomas A. (1985)
ABSTRACT NOT SUPPLIED.
Zugl.: Ithaca, NY, Cornell Univ., Diss.
Keywords: Database management; Operating systems (Computers); Synchronization; Hochschulschrift